2020
DOI: 10.1038/s41598-020-64086-1
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal drivers of oyster mortality: deciphering host, pathogen and environmental risk factors

Abstract: Diseases pose an ongoing threat to aquaculture, fisheries and conservation of marine species, and determination of risk factors of disease is crucial for management. our objective was to decipher the effects of host, pathogen and environmental factors on disease-induced mortality of Pacific oysters (Crassostrea gigas) across a latitudinal gradient. We deployed young and adult oysters at 13 sites in france and we monitored survival, pathogens and environmental parameters. the young oysters came from either the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 47 publications
3
19
0
Order By: Relevance
“…We assume that many more of the progenitors would have been latently infected based on our findings and from previous studies (Degremont & Benabdelmouna, 2014;Fleury et al, 2020;Jouaux et al, 2013;Paul-Pont et al, 2014). The lack of vertical transmission in all the batches of C. gigas progenies reported here most likely reflects an absence of key triggers for viral reactivation to occur in asymptomatic broodstock held in hatcheries, for example temperature and/or other environmental stressors.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…We assume that many more of the progenitors would have been latently infected based on our findings and from previous studies (Degremont & Benabdelmouna, 2014;Fleury et al, 2020;Jouaux et al, 2013;Paul-Pont et al, 2014). The lack of vertical transmission in all the batches of C. gigas progenies reported here most likely reflects an absence of key triggers for viral reactivation to occur in asymptomatic broodstock held in hatcheries, for example temperature and/or other environmental stressors.…”
supporting
confidence: 62%
“…Following epidemics driven by high water temperature in summer months, the putative latent infection persists in a proportion of the oyster population, with virus reactivation occurring weeks to months later (Dégremont et al, 2013; Fleury et al, 2020; Green et al, 2014; Jouaux et al, 2013; Segarra et al, 2014). Although temperature increase is well known as a key trigger of this disease, the mechanism that reactivates the infectious lytic cycle and also confirmation of latency is yet to be fully documented (Jouaux et al, 2013; Nguyen et al, 2019).…”
Section: Figurementioning
confidence: 99%
“…In different invertebrate–pathogen interactions, temperature has been found to affect the outcome of the interaction by influencing host and/or pathogen physiology ( 59 63 ). A permissive temperature range for POMS has been clearly identified, specifically, 16°C to 24°C ( 5 , 6 , 64 ). The same trend was observed in mesocosm experiments in which recipient oysters were confronted to disease donors at different temperature [ Figure 2A , ( 16 )].…”
Section: Poms Is a Multifactorial Diseasementioning
confidence: 97%
“…For decades, C. gigas has suffered from mortality due to disease ( 4 ), but the severity of these outbreaks has increased dramatically since 2008. These outbreaks affect the juvenile stages of the oyster, killing more than 35% of the cultivated and natural oysters in France every year ( 5 , 6 ). The corresponding syndrome, referred to as Pacific oyster mortality syndrome (POMS) ( 7 ), has become panzootic; it is observed in all the coastal regions of Franc, and in numerous other countries worldwide ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that environmental parameters, the physiological and genetic status of oysters, and the synergistic effects of pathogenic microorganisms may contribute to summer mortality (Tomaru et al, 2001; de Lorgeril et al, 2011;Genard et al, 2012). Seawater temperature, the amount of food, sea level atmospheric pressure, rainfall, and wind speed have all been associated with mortality risk (Fleury et al, 2020). Among all of the abiotic and biological factors that cause oyster mass mortality in summer, temperature rise is considered the most important (Le Roux et al, 2002;Gay et al, 2004;Meng et al, 2014).…”
Section: Introductionmentioning
confidence: 99%